Military Digital Diplomacy: A Case Study of the Japan Self- Defense Force on YouTube Platform - Wedagama, I Dewa Gede Radiantha; Ong, Susy (UI Scholars Hub, 2025)
This study examines the digital diplomacy strategies of the Japan Self-Defense Force (JSDF) through its engagement on the YouTube platform. It aims to analyze how the JSDF leverages digital media to reshape its international image, which has remained critically low since World War II, and to strengthen its soft power. Using a qualitative research approach, the study applies the 4D model of country image analysis, categorizing the JSDF’s digital content into functional, normative, aesthetic, and sympathetic dimensions. Data were collected through a comprehensive analysis of videos published on the JSDF's official YouTube channels, focusing on thematic content, user engagement metrics, and audience feedback. This analysis allowed for a deeper understanding of the strategies employed by the JSDF to portray its commitment to humanitarian missions, peacekeeping efforts, and national defense. The results show that the JSDF effectively uses YouTube to communicate its values of transparency, non-aggression, and technological advancement, aiming to shift perceptions and improve its standing on the global stage. Additionally, the study finds a predominantly positive reception from international audiences, suggesting a gradual shift in attitudes toward Japan's military, which has historically faced skepticism in the region. This research underscores the strategic potential of digital platforms in military diplomacy, highlighting the role of social media as a valuable tool for redefining national images, promoting a positive narrative, and fostering international dialogue and understanding.